Weakened carbon and nitrogen metabolisms under post-silking heat stress reduce the yield and dry matter accumulation in waxy maize - Huan YANG; Xiao-tian GU; Meng-qiu DING; Wei-ping LU; Da-lei LU (Journal of Integrative Agriculture, 2020)
Post-silking high temperature is one of the abiotic factors that affects waxy maize (Zea mays L. sinensis Kulesh) growth in southern China. We conducted a pot trial in 2016–2017 to study the effects of post-silking daytime heat stress (35°C) on the activities of enzymes involved in leaf carbon and nitrogen metabolisms and leaf reactive oxygen species (ROS) and water contents. This study could improve our understanding on dry matter accumulation and translocation and grain yield production. Results indicated that decreased grain number and weight under heat stress led to yield loss, which decreased by 20.8 and 20.0% in 2016 and 2017, respectively. High temperature reduced post-silking dry matter accumulation (16.1 and 29.5% in 2016 and 2017, respectively) and promoted translocation of pre-silking photoassimilates stored in vegetative organs, especially in leaf. The lower leaf water content and chlorophyll SPAD value, and higher ROS (H2O2 and O2−·) content under heat stress conditions indicated accelerated senescent rate. The weak activities of phosphoenolpyruvate carboxylase (PEPCase), Ribulose-1,5-bisphosphate carboxylase (RuBPCase), nitrate reductase (NR), and glutamine synthase (GS) indicated that leaf carbon and nitrogen metabolisms were suppressed when the plants suffered from a high temperature during grain filling. Correlation analysis results indicated that the reduced grain yield was mainly caused by the decreased leaf water content, weakened NR activity, and increased H2O2 content. The increased accumulation of grain weight and post-silking dry matter and the reduced translocation amount in leaf was mainly due to the increased chlorophyll SPAD value and NR activity. Reduced PEPCase and RuBPCase activities did not affect dry matter accumulation and translocation and grain yield. In conclusion, post-silking heat stress down-regulated the leaf NR and GS activities, increased the leaf water loss rate, increased ROS generation, and induced pre-silking carbohydrate translocation. However, it reduced the post-silking direct photoassimilate deposition, ultimately, leading to grain yield loss.